Phenotypic Alterations Involved in CD8+ Treg Impairment in Systemic Sclerosis - Negrini, Simone; Fenoglio, Daniela; Parodi, Alessia; Kalli, Francesca; Battaglia, Florinda; Nasi, Giorgia; Curto, Monica; Tardito, Samuele; Ferrera, Francesca; Filaci, Gilberto (Frontiers in Immunology, 2017)
Systemic sclerosis (SSc) is a connective tissue disease characterized by tissue fibrosis, vasculopathy and autoimmunity. Although the exact pathogenetic mechanisms behind SSc remain to be fully elucidated, a great deal of evidence suggests the existence of an unbalanced ratio between the effector and regulatory arms of the immune system. With regard to the Treg compartment, we observed that CD8+ Treg subsets display functional defects in SSc-affected patients. Since CD127 down-modulation and CD39 up-regulation have been observed on Treg subsets, the phenotypic expression of these molecules was analyzed on the CD8+CD28- Treg precursors and on CD8+ Treg cells generated in vitro through IL-10 commitment. Immunophenotypic data from SSc patients were compared to those obtained from healthy subjects. The analyses performed on ex vivo isolated CD8+CD28- Treg precursors did not show any significant differences in CD39 or CD127 expression as compared to values obtained from healthy donors. On the contrary, in vitro generated CD8+ Tregs obtained from SSc patients displayed reduced expression of the CD39 molecule as compared to controls. Moreover, the percentage of CD127+ cells was significantly higher in in vitro generated CD8+ Tregs from SSc patients compared to CD8+ Tregs obtained from healthy donors. Taken together, these findings may indicate an impairment of maturation processes affecting CD8+ Treg cells in SSc patients. This impairment of maturation involves phenotypic alterations and is that are mainly characterized by a deficient CD39 up-regulation and a lack of down-modulation of the CD127 molecule.